2016
DOI: 10.1039/c6cc07858c
|View full text |Cite
|
Sign up to set email alerts
|

A highly stable amino-coordinated MOF for unprecedented block off N2 adsorption and extraordinary CO2/N2 separation

Abstract: A highly stable amino-coordinated metal-organic framework ZJU-198 has been synthesized and structurally characterized, exhibiting high CO uptake of 105.8 cm cm while blocking off N adsorption at 1.0 bar and 298 K, attributed to the unique pore window sizes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 62 publications
(17 reference statements)
1
28
0
Order By: Relevance
“…We ascribe the drop in selectivity to the blocking of the narrower micropores (<1.0 nm) in HCP‐SC‐SO 3 ETA in addition to its lower nitrogen content compared to HCP‐SC‐SO 3 EN (Fig. ) . CO 2 /N 2 selectivity was lowest for HCP‐SC‐SO 3 TEA, where blocking of the narrower micropores and steric hindrance around the nitrogen lowered its selectivity to 6:1.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…We ascribe the drop in selectivity to the blocking of the narrower micropores (<1.0 nm) in HCP‐SC‐SO 3 ETA in addition to its lower nitrogen content compared to HCP‐SC‐SO 3 EN (Fig. ) . CO 2 /N 2 selectivity was lowest for HCP‐SC‐SO 3 TEA, where blocking of the narrower micropores and steric hindrance around the nitrogen lowered its selectivity to 6:1.…”
Section: Resultsmentioning
confidence: 90%
“…HCPs are formed by the extensive crosslinking of aromatic monomers, which upon solvent removal affords a strained polymer that is unable to fully collapse to a nonporous state . The diverse nature of the monomers available for the synthesis of HCPs (essentially any aromatic compound that possesses multiple reactive sites for Friedel–Crafts alkylation) offers potential advantages over other classes of microporous materials such as zeolites and MOFs . HCPs do not require the use of expensive catalysts in their synthesis .…”
Section: Introductionmentioning
confidence: 99%
“…MOF ZJU‐198 is a highly stable material formed by the organic linker 5‐amino‐H 2 L((2 E ,2 E ′)‐3,3′‐(5‐amino‐1,3‐phenylene) diacrylic acid) that coordinates with four Zn 2+ (empirical formula: C 12 H 7 NO 4 Zn). It has been reported that this structure separates CO 2 from N 2 , C 2 H 2 from CH 4 , and moderately C 2 H 2 from C 2 H 4 . This separation capability has been attributed to the channels of about 3.6×4.1 Å and 2.1×5.0 Å that exclude the molecule of nitrogen, and have low affinity for the molecule of methane.…”
Section: Figurementioning
confidence: 95%
“…This separation capability has been attributed to the channels of about 3.6×4.1 Å and 2.1×5.0 Å that exclude the molecule of nitrogen, and have low affinity for the molecule of methane. On the other hand, differences in the isosteric heat of adsorption of C 2 H 2 and C 2 H 4 allow this particular separation . Figure S1 of the Supporting Information shows the schematic connectivity of ZJU‐198.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation